User theory for inclusion or exclusion? Conceptual models to address the role of users for inclusive socio-technical change - Bortz, Gabriela Mijal (2022)
Innovation Studies (IS) and Science, Technology and Society studies (STS) exploredthe role of users in socio-technological change: from their role as consumers,adopters or experimenters to maximize profit, to exploring the mutual shaping ofusers and technologies and the power relations embedded into the process of use.By the turn of the century, amidst broader claims to democratize Science andTechnology, scholars and practitioners explored the ways technologies maycontribute to overcome social, material, and political restrictions in structuralinequality scenarios. While discursively praising user inclusion as a ‘good practice’,‘technologies for inclusive development’ (TID) ranged from processes of distributeddecision-making and empowerment to paternalistic schemes and unwanted effectsthat reinforce exclusion patterns. This paper aims to revisit user theories through thelens of inclusion/exclusion to explore user engagement in TID initiatives tounderstand the relation between user involvement and ‘inclusive’ outcomes. We arguethat diverse theoretical views on user-centeredness, which we systematize in 5 types,are tied to different normative assumptions about what user-centeredness is for, withimplications for technology practice and STS theory. In interaction between literaturereview and instrumental TID case studies (in water, health, nutrition, and recycling),we examine how these differences lead to differential outcomes in terms of inclusion(e.g., exclusion problem-solving, distribution of benefits, social learning). In turn, weanalyze how bringing the inclusiveness/exclusion dimension may help to reveal userliterature blind spots that need to be addressed, and how unveiling user theory maycontribute to deepen our understanding of inclusion in technology making.